Money and fame an experimental approach to determining the effect of monetary and recognition incentives on students' test-taking performance - Barreiro, Carlos Aurelio C. (School of Economics, University of the Philippines Diliman, 2019)
A major assumption in microeconomics is that extrinsic incentives improve performance. Better understanding on the effectivity of different extrinsic incentives on academic performance is key for creating incentive structures to improve students_ learning. This study aims to learn more about the effectivity of monetary compensation and recognition as incentives to improve university students_ test_taking performance by conducting a classroom experiment on students of the University of the Philippines Diliman. The experiment consisted of dividing students into three groups, control, monetary incentive, and recognition incentive. Each group was made to take a uniform baseline and endline test. The control group was not offered any incentive. The monetary incentive group was offered Php 5.0 per correct answer on the endline test. The recognition incentive was offered online recognition on the social media platform Facebook for the five highest endline scorers. Wilcoxon Rank_Sum Tests and Random Effects GLS Regressions were used in the analysis of the test scores. The Wilcoxon Rank_Sum Tests showed that median baseline scores did not significantly differ among control and treatment groups while median endline scores had significant differences especially among top_performing students. On the other hand, the interaction term in the panel data regression was not significant at a 95 percent confidence interval.